THE REALIZATION OF TENOR IN THE CONVERSATION TEXTS FOUND IN GRADE X ENGLISH TEXTBOOKS â€œPATHWAY TO ENGLISHâ€ AND â€œBAHASA INGGRIS KELAS X - Achsan, Mohamad; Sofwan, Ahmad (Universitas Negeri Semarang, 2016)
This study aims at explaining the tenor of the interactants in the conversation texts found grade X English textbooks as well as the appropriacy of their realization in the given contexts. This study also explains the similarities and differences between conversation texts found in both English textbooks in realizing tenor. This study was a qualitative research employing a descriptive comparative method. The comparative method compares conversation texts found in two English textbooks entitled â€œPathway to Englishâ€ and â€œBahasa Inggris Kelas Xâ€ to find their similarities and differences in realizing tenor. The result of lexicogrammatical analysis of conversation texts found in two English textbooks showed the texts of two textbooks were dominated by declarative. This meant that the mood in the models of the conversation texts tended giving information rather than demanding information or demanding goods and services. They were between teacher and student, student and student, and friend and friend. Furthermore, there were various statuses found in these texts. They were unequal and equal. At last, the social distances showed low contact and low affective involvement and high contact and high affective involvement.